RELATIONSHIP BETWEEN TEXT IN THE WORKS OF JALALUDDIN RUMI AND ALISHER NAVOI - Ganiev Ilhom Muzaffarovich; Ganieva Afifa Ilhomovna (Bright Mind Publishing, 2025)
The article discusses intertextuality in the works of Jalaluddin Rumi and Alisher Navoi and the factors that created it. Intertextuality has a biographical character, and its close connection with the creator's attitude to the world and man, forms of poetic perception of existence, and philosophical and mystical views is examined, and some conclusions are expressed.